2017
DOI: 10.1037/tra0000202
|View full text |Cite
|
Sign up to set email alerts
|

A latent profile analysis of intimate partner victimization and aggression and examination of between-class differences in psychopathology symptoms and risky behaviors.

Abstract: Objective Intimate partner violence (IPV) is associated with heightened psychopathology symptoms and risky behaviors. However, extant investigations are limited by their focus on IPV victimization, despite evidence to suggest that victimization and aggression frequently co-occur. Further, research on these correlates often has not accounted for the heterogeneity of women who experience victimization. Method The present study utilized latent profile analysis to identify patterns of physical, psychological, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 53 publications
5
21
0
Order By: Relevance
“…After removing duplicates, we short-listed 442 unique articles. We identified two additional articles outside the database search; one study was published after our initial search and identified by an author (Weiss et al, 2016), and another study was identified through secondary screening (Carbone-López, Kruttschnitt, & Macmillan, 2006). In total, two coauthors reviewed 444 abstracts, and excluded 348 articles based on abstract review.…”
Section: Resultsmentioning
confidence: 99%
“…After removing duplicates, we short-listed 442 unique articles. We identified two additional articles outside the database search; one study was published after our initial search and identified by an author (Weiss et al, 2016), and another study was identified through secondary screening (Carbone-López, Kruttschnitt, & Macmillan, 2006). In total, two coauthors reviewed 444 abstracts, and excluded 348 articles based on abstract review.…”
Section: Resultsmentioning
confidence: 99%
“…Future studies are needed to clarify the role of the different facets of positive emotional experiences in heavy drinking and drug use, including responses to versus quality of (e.g., see Weiss et al, 2015 for a measure of difficulties regulating positive emotions) positive emotions. Given evidence here for higher levels of positive affect lability among trauma-exposed individuals, it also will be important for future investigations to identify the contribution of positive affect lability to other health consequences, including risky behaviors (e.g., risky sexual behavior) and psychopathology (e.g., posttraumatic stress; Chen et al, 2010; Weiss, Dixon-Gordon, et al, in press).…”
Section: Discussionmentioning
confidence: 99%
“…Two studies by Weiss and colleagues (Weiss et al ., ; Weiss, Dixon‐Gordon, Duke and Sullivan, ) sought to explain the mediating factors which underlie the relationship between IPV and self‐harm. Weiss et al .…”
Section: Overview Of Key Findingsmentioning
confidence: 99%
“…Weiss et al . 's () study of 212 community women experiencing victimization examined the associations between physical, sexual and psychology victimization and aggression, psychopathology and risky behaviours such as self‐harm, substance abuse and HIV‐risk behaviours. Greater psychopathology symptoms were found among women defined by greater victimization and aggression, regardless of IPV type.…”
Section: Overview Of Key Findingsmentioning
confidence: 99%
See 1 more Smart Citation